Brazilian clays for environmental solutions applied to radioactive waste management - Gabriel Gonzalo Machado; Victoria Krupskaya; Sergey V Zakusin; Julio HARADA; Rodrigo Papai de Souza; Leandro Goulart Araujo; Denise Crocce Espinosa; Edy L.T. Montalvan; Henrique Kahn; Roberto Vicente; Sabine Guilhen (Brazilian Journal of Radiation Sciences, 2021)
Clays have been adopted in most nuclear waste producing countries as a key constituent in engineered barrier systems for final disposal facilities at all levels of radioactive wastes (LILW-SL, LILW-LL, and HLW). The following study presents a thorough characterization upon five Brazilian clay-rich deposits, mostly smectite bearing clays, aiming to evaluate their expected performance as barrier under the conditions associated to a Low and Intermediate Level Waste Repository; being the former a matter of national strategic interest. Samples coming from the Brazilian states of Paraná, Bahia, Paraíba, and Maranhão were treated and analyzed by means of X-Ray diffraction as main technique, and complemented by FTIR, LALLS, XRF, and SEM-EDS, in order to establish the mineralogical composition, particle size distribution, and chemical composition. Moreover, several standard clay treatments over the <1 μm size fraction were carried out to reveal information regarding layer charge, major interlayer cations, unit formula and other crystal features of smectite species present in a mineralogical assembly, aiming to provide information for the construction of a molecular model over which would be realistic to simulate the diffusion of radionuclides. Results obtained on 133Cs adsorption experiments indicate that mineralogical composition would probably be the single most influential factor controlling transport capacity of positively charged radionuclides in the current setup. The composition is especially expressed in terms of smectite contents, favoring montmorillonite rich materials containing majorly Na+ as compensating cation in interlayer position. All tested samples can be considered as suitable candidates to be used in the design of final destination storage for nuclear waste. Thus, efficiency on 133Cs adsorption trials also indicate that these materials could have potential uses as sorptive matrices (Sorbents) for water treatment of radionuclide polluted waters such as TENORM waste waters. However, these trends are yet to be contrasted against hydraulic conductivity measurements and swelling pressure in order to have a more comprehensive perspective of this clayey prospects as barrier enhanced layer; aligned to the multilayer barrier system approach for nuclear waste management.